Competitive Agriculture or State Control : Ukraine's Response to the Global Food Crisis - World Bank (Washington, DC, 2014)
World market prices for grains and oilseeds have risen dramatically over the last 24 months. Despite a recent drop, wheat prices are still about twice what they were two years ago. Given the underlying causes, this situation is likely to persist for the medium term (International Food Policy Research Institute-IFPRI and World Bank projections use a time horizon until 2015). Rising food prices are causing significant hardship worldwide and threatening to cast large numbers of people into poverty. However, the current situation is a major opportunity for Ukraine, a net grain exporter with a significant exploitable yield gap and one of the few countries in the world that are in a position to significantly increase net exports and make up for emerging deficits elsewhere. With appropriate policies and investments, Ukraine could significantly increase its grain harvest and gain global market share in an environment of rising global demand. Even relatively conservative estimates of growth in yields and acreage indicate that a regular harvest of over 40 million tons will be possible. Seizing this opportunity will require a shift in policies and corresponding increases in private and public investment. Ukraine is in a position to make a significant contribution to the international effort to deal with the food crisis, while providing attractive investment and employment opportunities in the agriculture sector (in rural areas) that are expected to yield significant income, trade, and fiscal benefits.